Lithium manganese iron phosphate materials and their preparation methods, secondary batteries and power devices
By coating lithium iron phosphate with fluorine-containing passivators and carbon materials, the problems of poor conductivity and structural stability of lithium iron phosphate were solved, achieving high conductivity and stability of the material and improving the cycle performance and capacity of the battery.
Patent Information
- Application Number
- CN202511021409.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-07-24
AI Technical Summary
Existing lithium manganese iron phosphate materials suffer from low conductivity and poor structural stability, which affect the cycle performance and capacity utilization of batteries.
The core of lithium manganese iron phosphate is coated with lithium iron phosphate, and fluorine-containing passivation material and carbon material are added to the shell. The mass percentages of fluorine and carbon elements are 0.5%~2.0% and 1.0%~2.0%, respectively, forming a fluorine-containing passivation layer and a carbon layer, which enhances the structural stability and conductivity of the material.
The conductivity and structural stability of lithium manganese iron phosphate materials were improved, thereby enhancing the cycle performance and capacity utilization of the battery.
Smart Images

Figure CN120527376B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, specifically to a lithium manganese iron phosphate material and its preparation method, a secondary battery and an electrical device. Background Technology
[0002] Secondary batteries are widely used in various consumer electronics and electric vehicles due to their outstanding characteristics such as light weight, no pollution, and no memory effect. Among them, lithium-ion batteries have a very wide range of applications in portable electronic devices and electric vehicles.
[0003] As the application of rechargeable batteries becomes more and more widespread, the requirements for battery performance are also becoming higher and higher. Summary of the Invention
[0004] In view of the above problems, this application provides a lithium manganese iron phosphate material and its preparation method, a secondary battery and an electrical device. The lithium manganese iron phosphate material has good structural stability and strong conductivity, which makes it convenient for the battery to simultaneously achieve good cycle performance and specific capacity.
[0005] The first aspect of this application is to provide a lithium manganese iron phosphate material, including a core and a shell, wherein the core is lithium manganese iron phosphate coated with lithium iron phosphate;
[0006] The aforementioned outer shell is located on at least a portion of the surface of the core;
[0007] The aforementioned shell comprises fluorine-containing passivation material and carbon material. Based on the total mass of the aforementioned lithium manganese iron phosphate material, the mass percentage content of fluorine is 0.5% to 2.0%, and the mass percentage content of carbon is 1.0% to 2.0%.
[0008] This application uses lithium iron phosphate to coat lithium manganese iron phosphate, and the outer shell contains carbon materials, which is beneficial to improving the conductivity of lithium manganese iron phosphate. The outer shell also includes a fluorinated passivator, which is located on at least part of the surface of the core. The fluorinated passivator itself has good stability, which increases the structural stability of lithium manganese iron phosphate and lithium iron phosphate in the core. At the same time, this application selects the fluorine and carbon content that matches the above coating structure, so that the lithium manganese iron phosphate material can take into account both good structural stability and strong conductivity.
[0009] In some embodiments, along a direction away from the core, the outer casing sequentially includes a fluorinated passivation layer and a carbon layer, the fluorinated passivation layer covering the surface of lithium iron phosphate, and the carbon layer covering the surface of the fluorinated passivation layer; the fluorinated passivation layer includes the fluorinated passivant, and the carbon layer includes the carbon material.
[0010] The fluorinated passivation layer of this application is located on the entire surface of the core. The fluorinated passivation material in the fluorinated passivation layer has good stability, which increases the structural stability of lithium manganese iron phosphate and lithium iron phosphate in the core. In addition, the carbon layer is coated on the surface of the fluorinated passivation layer. The carbon layer has good conductivity, which effectively makes up for the conductivity defects of the fluorinated passivation layer. Therefore, the lithium manganese iron phosphate material provided by this application has the advantages of both good structural stability and strong conductivity.
[0011] In some embodiments, the fluorine-containing passivator and carbon material constitute a shell for covering the core.
[0012] In this application, the fluorine-containing passivator in the coating layer is uniformly mixed with the carbon material, and the two work together to improve the structural stability and conductivity of the lithium manganese iron phosphate material.
[0013] In some embodiments, the fluorinated passivator described above includes a metal fluoride;
[0014] The aforementioned metal fluorides include any one or more of aluminum fluoride, lithium fluoride, and sodium fluoride.
[0015] The aluminum fluoride, lithium fluoride, and sodium fluoride listed in this application facilitate better improvement of the structural stability of lithium manganese iron phosphate materials.
[0016] In some embodiments, the carbon material described above includes nitrogen-doped carbon material, wherein the mass percentage content of nitrogen element is 0.5% to 2.0% based on the total mass of the nitrogen-doped carbon material.
[0017] In some embodiments of this application, the carbon material selected includes nitrogen-doped carbon material. Compared with undoped carbon material, nitrogen-doped carbon material introduces active sites, which further improves the conductivity of electrons and ions of lithium manganese iron phosphate material.
[0018] In some embodiments, the mass of the lithium iron phosphate is 11% to 43% of the mass of lithium manganese iron phosphate.
[0019] As described above, the core of this application is lithium iron phosphate coated with lithium manganese iron phosphate, wherein lithium iron phosphate is completely coated on the surface of lithium manganese iron phosphate, forming a coating layer with appropriate content or thickness. This coating layer can improve the conductivity of lithium manganese iron phosphate material and reduce the dissolution of manganese from lithium manganese iron phosphate material. However, lithium iron phosphate has a lower specific capacity than lithium manganese iron phosphate. Therefore, in order to balance specific capacity, conductivity and structural stability, this application selects lithium iron phosphate to have a mass of 11% to 43% of the mass of lithium manganese iron phosphate.
[0020] In some embodiments, the specific surface area of the lithium iron phosphate coated lithium manganese iron phosphate particles is 1.0 m². 2 / g~5.0m 2 / g.
[0021] As described above, lithium iron phosphate completely coats the surface of lithium manganese iron phosphate, forming a coating layer with appropriate content or thickness. Compared with uncoated lithium manganese iron phosphate, the particle specific surface area of lithium iron phosphate coated with lithium iron phosphate is reduced.
[0022] The second aspect of this application is to provide a method for preparing lithium manganese iron phosphate material.
[0023] Take the first iron source, manganese source, first phosphorus source and first lithium source and mix them evenly to obtain a mixture;
[0024] The above mixture was ground and calcined to obtain lithium manganese iron phosphate seed crystals;
[0025] Lithium manganese iron phosphate coated with lithium iron phosphate is prepared by mixing the second iron source, the second phosphorus source, the second lithium source with the above-mentioned lithium manganese iron phosphate seed crystal and then reacting them with hydrothermal reaction.
[0026] The lithium manganese iron phosphate material was prepared by reacting the lithium iron phosphate-coated lithium manganese iron phosphate with fluorine-containing components and a carbon source.
[0027] In some embodiments, the volumetric particle size Dv50 of the above-mentioned lithium manganese iron phosphate seed crystal is 100nm~200nm;
[0028] And / or, the above grinding is ultrafine grinding, which is ultrafine grinding to a particle volume diameter (Dv50) of 0.1 μm to 3 μm;
[0029] And / or, the above-mentioned calcination is low-temperature calcination, the temperature of which is 600℃~650℃ and the calcination time is 6h~15h.
[0030] In some embodiments, the heating rate of the above-mentioned hydrothermal reaction is 1℃ / min~5℃ / min, the temperature is raised to 160℃~240℃, and the hydrothermal reaction lasts for 10h~24h.
[0031] and / or;
[0032] The first iron source and the second iron source mentioned above are each independently selected from any one or more of ferrous sulfate, ferrous acetate, ferrous chloride, and ferrous nitrate.
[0033] A third aspect of this application is to provide a secondary battery comprising the lithium manganese iron phosphate material described in the first aspect or the lithium manganese iron phosphate material prepared by the preparation method described in the second aspect.
[0034] The lithium manganese iron phosphate material provided in this application has good structural stability and strong conductivity, which makes it convenient for batteries to simultaneously achieve good cycle performance and specific capacity.
[0035] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description
[0036] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0037] Figure 1 This is a schematic diagram of the battery structure of some embodiments of this application;
[0038] Figure 2 This is an exploded structural diagram of a battery according to some embodiments of this application;
[0039] Figure 3 This is a schematic diagram of the vehicle structure according to some embodiments of this application;
[0040] Figure 4 This is a schematic diagram of the battery pack structure according to some embodiments of this application;
[0041] Figure 5 This is a schematic diagram of the structure of lithium manganese iron phosphate material according to some embodiments of this application;
[0042] Figure 6 These are transmission electron microscope (TEM) images of lithium manganese iron phosphate materials according to some embodiments of this application, wherein 6A and 6B are TEM images at different magnifications.
[0043] The reference numerals in the detailed embodiments are as follows:
[0044] 10000, vehicles;
[0045] 1000, Battery; 2000, Controller; 3000, Motor;
[0046] 100. Battery cell; 101. Casing; 102. Electrode assembly; 103. Cover plate;
[0047] 200. Box body; 210. First part; 220. Second part;
[0048] 10. Secondary batteries;
[0049] 11. Lithium iron manganese phosphate materials;
[0050] 11a. Kernel;
[0051] 11b. Fluorine-containing passivation layer;
[0052] 11c, carbon layer. Detailed Implementation
[0053] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the positive electrode, secondary battery, battery pack, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0054] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0055] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0056] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0057] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0058] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0059] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0060] Unless otherwise specified, in this application, the terms "first," "second," etc., are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features.
[0061] Unless otherwise specified, in this application, the term "multiple" means two or more (including two), similarly, "multiple sets" means two or more (including two sets), and "multiple pieces" means two or more (including two pieces).
[0062] Unless otherwise specified, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0063] Secondary batteries
[0064] In this application, a secondary battery refers to a battery cell that can be recharged after it has been discharged, allowing the active materials to be activated and reused.
[0065] The secondary battery can be a lithium-ion battery, sodium-ion battery, sodium-lithium-ion battery, lithium metal battery, sodium metal battery, lithium-sulfur battery, magnesium-ion battery, nickel-metal hydride battery, nickel-cadmium battery, lead-acid battery, etc., and the embodiments of this application are not limited to this.
[0066] Electrode assembly
[0067] A secondary battery typically includes an electrode assembly. This assembly comprises a positive electrode, a negative electrode, and a separator, with the separator positioned between the positive and negative electrodes. During the charging and discharging process of a secondary battery, active ions (such as lithium ions) repeatedly insert and extract between the positive and negative electrodes. The separator, located between the positive and negative electrodes, prevents short circuits while allowing active ions to pass through.
[0068] Battery device
[0069] The battery apparatus mentioned in the embodiments of this application may include one or more battery cell assemblies for providing voltage and capacity. A battery cell assembly may include multiple battery cells connected in series, parallel, or mixed connections via a busbar.
[0070] In some embodiments, a battery cell assembly is typically formed by arranging multiple battery cells.
[0071] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple battery cells together with cable ties.
[0072] In some embodiments, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.
[0073] As an example, the battery cell assembly can be a battery module, and the battery cell assembly can be housed in the housing by fixing the battery module in the housing.
[0074] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple battery cells to the housing.
[0075] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.
[0076] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.
[0077] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.
[0078] The battery cell of this application may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte composed of the aforementioned battery cell. The outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging of the battery cell can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic, including but not limited to polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0079] This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 This is an example of a square-structured secondary battery 10.
[0080] According to some embodiments of this application, reference is made to Figure 2 The outer packaging may include a housing 101 and a cover plate 103. The housing 101 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 101 has an opening communicating with the receiving cavity, and the cover plate 103 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 102 by a winding process or a stacking process. The electrode assembly 102 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 102. The secondary battery 10 may contain one or more electrode assemblies 102, which can be selected by those skilled in the art according to specific practical needs.
[0081] The electrode assembly 102 provided in this application is beneficial to improving the performance of a battery cell when applied in a battery cell. The battery cell can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is used in the power field, such as mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited to the above fields.
[0082] For ease of explanation, some embodiments of this application are illustrated using a vehicle as an example of an electrical device.
[0083] Please refer to Figure 3 , Figure 3 This is a schematic diagram of the structure of a vehicle 10000 provided in some embodiments of this application. The vehicle 10000 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A battery 1000 is disposed inside the vehicle 10000, and the battery 10000 can be located at the bottom, front, or rear of the vehicle 10000. The battery 10000 can be used to power the vehicle 10000; for example, the battery 10000 can serve as the operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000. The controller 2000 is used to control the battery 10000 to supply power to the motor 3000, for example, to meet the power needs of the vehicle 10000 during startup, navigation, and driving.
[0084] In some embodiments of this application, the battery 1000 can not only serve as the operating power source for the vehicle 10000, but also as the driving power source for the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.
[0085] Please refer to Figure 4 , Figure 4 This is an exploded view of a battery 1000 provided in some embodiments of this application. The battery 1000 includes a housing 200 and a battery cell 100. A conventional battery cell includes a primary battery or a secondary battery. This application specifically protects a secondary battery 10. The battery cell 100 is housed within the housing 200. The housing 200 provides space for the battery cell 100, and the housing 200 can adopt various structures.
[0086] In some embodiments, the housing 200 may include a first portion 210 and a second portion 220, which overlap each other, and together define a receiving space for accommodating the battery cell 100. The second portion 220 may be a hollow structure with one open end, and the first portion 210 may be a plate-like structure, with the first portion 210 covering the open side of the second portion 220 so that the first portion 210 and the second portion 220 together define the receiving space; alternatively, the first portion 210 and the second portion 220 may both be hollow structures with one open side, with the open side of the first portion 210 covering the open side of the second portion 220. Of course, the housing 200 formed by the first portion 210 and the second portion 220 may be of various shapes, such as a cylinder, a cuboid, etc.
[0087] In battery 1000, there can be multiple battery cells 100, which can be connected in series, parallel, or in a mixed manner. A mixed connection means that multiple battery cells 100 are connected in both series and parallel configurations. Multiple battery cells 100 can be directly connected in series, parallel, or in a mixed manner, and then the entire assembly of the multiple battery cells 100 is housed within housing 200. Alternatively, battery 1000 can also be composed of multiple battery cells 100 first connected in series, parallel, or in a mixed manner to form battery modules, and then these modules are connected in series, parallel, or in a mixed manner to form a whole, which is also housed within housing 200. Battery 1000 may also include other structures; for example, it may include a busbar component for electrical connection between the multiple battery cells 100.
[0088] Lithium manganese iron phosphate
[0089] Lithium manganese iron phosphate (LMP), an upgraded version of lithium iron phosphate, was developed to further improve energy density while retaining the safety and cycle advantages of phosphates. However, LMP is an insulator with low conductivity, and the leaching of manganese from its interior leads to low structural stability.
[0090] To alleviate the above problems, related technologies disclose coating lithium iron phosphate onto the surface of lithium manganese iron phosphate, wherein the olivine-structured lithium iron phosphate has an electrical conductivity of 10 at room temperature. -9 S / cm, lithium manganese iron phosphate with olivine structure has a conductivity of 10 at room temperature. -13The conductivity of lithium iron phosphate (LFP) is increased by coating lithium manganese iron phosphate (LFP) with S / cm. However, manganese and iron dissolve within LFP, resulting in limited improvement in structural stability. Related technologies also disclose coating LFP with stable materials to isolate it from the external environment and increase its structural stability. However, these stable materials do not possess electron or ion conduction capabilities, thus reducing the conductivity of LFP.
[0091] In view of this, this application discloses a lithium manganese iron phosphate material, which includes a core and a shell. The core is lithium manganese iron phosphate coated with lithium iron phosphate. The shell is located on at least a portion of the surface of the core. The shell includes a fluorine-containing passivator and a carbon material. Based on the total mass of the lithium manganese iron phosphate material, the mass percentage content of fluorine is 0.5% to 2.0%, and the mass percentage content of carbon is 1.0% to 2.0%.
[0092] This application uses lithium iron phosphate to coat lithium manganese iron phosphate, and the outer shell contains carbon materials, which is beneficial to improving the conductivity of lithium manganese iron phosphate. The outer shell also includes a fluorinated passivator, which is located on at least part of the surface of the core. The fluorinated passivator itself has good stability, which increases the structural stability of lithium manganese iron phosphate and lithium iron phosphate in the core. At the same time, this application selects the fluorine and carbon content that matches the above coating structure, so that the lithium manganese iron phosphate material can take into account both good structural stability and strong conductivity.
[0093] The core of this application is lithium iron phosphate coated with lithium manganese iron phosphate. The method for distinguishing between lithium iron phosphate and lithium manganese iron phosphate includes obtaining a transmission electron microscope (TEM) image of the lithium manganese iron phosphate material. Since lithium iron phosphate and lithium manganese iron phosphate exhibit different lattice fringes, it can be determined that the core is composed of two different components. Furthermore, X-ray diffraction (XRD) patterns of these two different components are obtained, and lithium iron phosphate and lithium manganese iron phosphate are identified respectively based on the interplanar spacing.
[0094] Meanwhile, the structure of the lithium manganese iron phosphate material of this application can be determined by composition determination, which includes any conventional determination method in the art, such as the combination of energy-dispersive X-ray spectroscopy (EDS) and transmission electron microscopy (TEM). The specific test steps are as follows:
[0095] The elemental composition of lithium manganese iron phosphate materials was analyzed by combining energy-dispersive X-ray spectroscopy (EDS) of model ISC150 with transmission electron microscopy (TEM) of model ZEISS. Specifically, EDS was used to detect the material and perform point analysis; the scanning electron beam moved across the sample surface, recording the intensity of characteristic X-rays at different locations to generate an elemental distribution map for surface analysis; the detector collected characteristic X-rays and converted them into electrical signals, which were then processed by a multichannel pulse height analyzer. By detecting the energy distribution of these X-rays, the types of elements in the sample could be determined. By measuring the intensity of characteristic X-rays and comparing them with known standard samples, a semi-quantitative analysis of elemental content could be achieved, thereby identifying the core and shell, as well as the elemental composition within the shell.
[0096] The carbon content in the shell of this application can also be determined by other methods conventional in the art, such as referring to GB / T 20123-2006 / ISO 15350:2000, with the HCS-140 infrared carbon-sulfur analyzer as the testing instrument.
[0097] The core of this application is located inside the shell, the shell is located outside the core, and the shell is located on at least a portion of the surface of the core. Here, at least a portion of the surface includes both partial and complete surfaces. In specific embodiments, this application mainly uses the complete surface as an example to illustrate this application.
[0098] The fluorinated passivator in this application refers to a compound or mixture containing fluorine and having relatively stable properties. When lithium manganese iron phosphate is used in a battery, the fluorinated passivator does not react with the battery electrolyte and isolates lithium iron phosphate and lithium manganese iron phosphate from the electrolyte, reducing interfacial side reactions on the surface of the cathode material and maintaining the structural stability of lithium iron phosphate and lithium manganese iron phosphate.
[0099] This application controls the mass percentage of fluorine in the lithium manganese iron phosphate material to be 0.5%~2.0% and the mass percentage of carbon in the lithium manganese iron phosphate material to be 1.0%~2.0%. By selecting the fluorine and carbon content that matches the above coating structure, the lithium manganese iron phosphate material can take into account both the advantages of good structural stability and strong conductivity.
[0100] In these embodiments, this application discloses that the total mass of the lithium manganese iron phosphate material contains fluorine in any one of the following: 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or any one of the ranges of both of the above.
[0101] In these embodiments, this application discloses that the total mass of the lithium manganese iron phosphate material has a carbon element mass percentage content of any one of 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or any one of the above ranges.
[0102] In some embodiments, fluorinated passivators are mixed with carbon materials to form a coating layer for coating the core. The fluorinated passivators and carbon materials in the coating layer are mixed evenly, and the two work together to improve the structural stability and conductivity of lithium manganese iron phosphate materials.
[0103] In some embodiments, along a direction away from the core, the outer casing sequentially includes a fluorinated passivation layer and a carbon layer, wherein the fluorinated passivation layer covers the surface of the lithium iron phosphate, and the carbon layer covers the surface of the fluorinated passivation layer;
[0104] The aforementioned fluorine-containing passivation layer includes the aforementioned fluorine passivator, and the aforementioned carbon layer includes the aforementioned carbon material.
[0105] like Figure 5 The illustration shows that the lithium manganese iron phosphate material includes a core and a shell. The core is lithium manganese iron phosphate coated with lithium iron phosphate. The shell is located on the entire surface of the core. Along the direction away from the core, the shell sequentially includes a fluorinated passivation layer and a carbon layer. The fluorinated passivation layer covers the surface of the lithium iron phosphate, and the carbon layer covers the surface of the fluorinated passivation layer. The fluorinated passivation layer includes the aforementioned fluorinated passivation material, and the carbon layer includes the aforementioned carbon material.
[0106] The fluorinated passivation layer of this application is located on the entire surface of the core. The fluorinated passivation material in the fluorinated passivation layer has good stability, which increases the structural stability of lithium manganese iron phosphate and lithium iron phosphate in the core. In addition, the carbon layer is coated on the surface of the fluorinated passivation layer. The carbon layer has good conductivity, which effectively makes up for the conductivity defects of the fluorinated passivation layer. Therefore, the lithium manganese iron phosphate material provided by this application has the advantages of both good structural stability and strong conductivity.
[0107] The structure of the lithium manganese iron phosphate material of this application can be obtained by combining energy dispersive X-ray spectroscopy (EDS) with transmission electron microscopy (TEM).
[0108] In some embodiments, the fluorinated passivator includes a metal fluoride; the metal fluoride includes one or more of aluminum fluoride, lithium fluoride, and sodium fluoride.
[0109] The metal fluoride provided in this application has relatively stable properties, which is beneficial to improving the structural stability of lithium manganese iron phosphate materials, and has little impact on the conductivity of electrons and ions of lithium manganese iron phosphate materials.
[0110] The aluminum fluoride, lithium fluoride, and sodium fluoride listed in this application facilitate better improvement of the structural stability of lithium manganese iron phosphate materials.
[0111] In some embodiments, the carbon material described above includes nitrogen-doped carbon material, wherein the mass percentage content of nitrogen element is 0.5% to 2.0% based on the total mass of the nitrogen-doped carbon material.
[0112] The carbon material in this application can be shaped carbon or amorphous carbon formed by calcining a carbon source.
[0113] The carbon material in this application may also be nitrogen-doped shaped carbon or nitrogen-doped amorphous carbon formed by calcining carbon and nitrogen sources.
[0114] In some embodiments of this application, the carbon material selected includes nitrogen-doped carbon material. Compared with undoped carbon material, nitrogen-doped carbon material introduces active sites, which further improves the conductivity of electrons and ions of lithium manganese iron phosphate material.
[0115] In these embodiments, the mass ratio of nitrogen is controlled, and by introducing an appropriate amount of active sites, the conductivity of electrons and ions of lithium manganese iron phosphate materials can be improved.
[0116] In these embodiments, this application discloses that the total mass of nitrogen-doped carbon material contains nitrogen at any one of the following mass percentages: 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, and 2.0%, or any one of the ranges for both of the above.
[0117] In some embodiments, the mass of lithium iron phosphate is 11% to 43% of the mass of lithium manganese iron phosphate.
[0118] As described above, the core of this application is lithium iron phosphate coated with lithium manganese iron phosphate, wherein lithium iron phosphate is completely coated on the surface of lithium manganese iron phosphate, forming a coating layer with appropriate content or thickness. This coating layer can improve the conductivity of lithium manganese iron phosphate material and reduce the dissolution of manganese from lithium manganese iron phosphate material. However, lithium iron phosphate has a lower specific capacity than lithium manganese iron phosphate. Therefore, in order to balance specific capacity, conductivity and structural stability, this application selects lithium iron phosphate to have a mass of 11% to 43% of the mass of lithium manganese iron phosphate.
[0119] In these embodiments, this application discloses that the mass of lithium iron phosphate is any one of 11%, 11.5%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 23.1%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 42.2%, or 43% of the mass of lithium manganese iron phosphate, or any one of the ranges of both above.
[0120] As described above, the identification method for lithium iron phosphate (LFP) and lithium manganese iron phosphate (LMP) includes obtaining a transmission electron microscope (TEM) image of the LMP material. Since LFP and LMP exhibit different lattice fringes, it can be determined that the core is composed of two different components. Furthermore, X-ray diffraction (XRD) patterns of these two different components are obtained, and LFP and LMP are identified based on their interplanar spacing. Meanwhile, the LFP content can be further determined using conventional methods in the art.
[0121] In some embodiments, the specific surface area of the lithium iron phosphate coated lithium manganese iron phosphate particles is 1.0 m². 2 / g~5.0m 2 / g.
[0122] As described above, lithium iron phosphate completely coats the surface of lithium manganese iron phosphate, forming a coating layer with appropriate content or thickness. Compared with uncoated lithium manganese iron phosphate, the particle specific surface area of lithium iron phosphate coated with lithium iron phosphate is reduced.
[0123] Specific surface area refers to the surface area of particles measured using any method conventional in the field, such as the nitrogen adsorption specific surface area analysis method according to GB / T19587-2004, and the BET (Brunauer Emmett Teller) method to calculate the specific surface area of the particles. The testing instrument can be a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.
[0124] This application discloses in these embodiments that the specific surface area of lithium iron phosphate coated manganese iron phosphate particles is 1.0 m². 2 / g, 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 5.0m 2 Any one of / g or any one of the ranges of the above two.
[0125] In some embodiments, the chemical formula of lithium manganese iron phosphate in the above-mentioned core is Lib1 Fe c1 Mn d1 M 1-c1-d1 PO4.
[0126] In some embodiments, the chemical formula of lithium iron phosphate in the above-described core is Li. b2 Fe c2 M' 1-c2 PO4.
[0127] Where M represents the doping element at the manganese site and the iron site, M' represents the doping element at the iron site, and M and M' each independently include any one or more of Al, Cu, Mg, Zn, Ni, Ti, V, Zr, Co, Ga, Sn, Sb, and Nb;
[0128] In the chemical formula of lithium manganese iron phosphate in this application, b1 is 0.9 to 1.1; c1 is 0.001 to 0.999; d1 is 0.001 to 0.999; and 1-c1-d1 is 0 to 0.1.
[0129] In the chemical formula of lithium iron phosphate in this application, b2 is 0.9 to 1.1; c2 is 0.001 to 1.
[0130] The lithium manganese iron phosphate and lithium iron phosphate of this application can be prepared in-house. The components of the lithium manganese iron phosphate and lithium iron phosphate of this application can also be detected using commonly used chemical analysis methods in the field, including but not limited to: complexation titration, precipitation gravimetric method, redox method, differential method, inductively coupled plasma atomic emission spectrometry (ICP-AES), and atomic absorption spectrometry. Among these, ICP-AES and atomic absorption spectrometry are convenient and efficient, and their mechanisms are as follows:
[0131] Plasma emission spectroscopy is an analytical method that uses a high-temperature excitation source generated by plasma as the excitation source for atomic emission spectra. Different elements produce different characteristic spectra. These characteristic spectra are projected onto a grating in a spectrometer through a lens. By controlling a motor to rotate the grating, a transmission mechanism accurately positions the intensity of the characteristic spectral lines of the element to be measured at the exit slit after spectral dispersion. A photomultiplier tube converts this spectral intensity into an electric current. After further circuit processing and conversion, the data is processed by a computer to obtain the analytical results.
[0132] Atomic absorption spectrometry (AAS), also known as atomic absorption spectrophotometry, is an analytical method based on the absorption of characteristic radiation (spectral lines) emitted by atomic vapors of the same type of atom. The analytical process involves irradiating the sample solution with atomized and atomized atomic vapors of the sample solution using characteristic radiation emitted by the same type of atom. The gaseous ground-state atoms of the analyte in the vapor absorb the characteristic radiation lines emitted from the light source. Different elements exhibit selective absorption of these characteristic radiation lines, and the concentration of the analyte in the sample is determined by the degree of radiation attenuation.
[0133] In these embodiments, this application discloses that the chemical formula of lithium manganese iron phosphate in the core is b1, which is any one of 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1 or any one of the above two ranges.
[0134] In these embodiments, this application discloses that the chemical formula of lithium manganese iron phosphate has c1 that is any one of 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99, or 0.999, or any one of the ranges of both of the above.
[0135] In these embodiments, this application discloses that d1 is any one of 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99, 0.999 or any one of the ranges of the above two values.
[0136] In these embodiments, this application discloses that b2 is any one of 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1 or any one of the ranges of both above.
[0137] In these embodiments, this application discloses that c2 is any one of 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99, 0.999, 1 or any one of the ranges of the above two values.
[0138] This application discloses in these embodiments that the chemical formula of lithium manganese iron phosphate in the core is Li. b1 Fe 0.45~ 0.55 Mn 0.45~0.55 PO4.
[0139] Preparation method of lithium manganese iron phosphate material
[0140] To obtain lithium manganese iron phosphate material with the above-described structure and composition, this application discloses a method for preparing lithium manganese iron phosphate material in some embodiments, the method comprising:
[0141] Take the first iron source, manganese source, first phosphorus source and first lithium source and mix them evenly to obtain a mixture;
[0142] The above mixture was ground and calcined to obtain lithium manganese iron phosphate seed crystals;
[0143] Lithium manganese iron phosphate coated with lithium iron phosphate is prepared by mixing the second iron source, the second phosphorus source, the second lithium source with the above-mentioned lithium manganese iron phosphate seed crystal and then reacting them with hydrothermal reaction.
[0144] The lithium manganese iron phosphate material was prepared by reacting the lithium iron phosphate-coated lithium manganese iron phosphate with fluorine-containing components and a carbon source.
[0145] The preparation method provided in this application facilitates the preparation of lithium manganese iron phosphate materials with good structural stability and strong conductivity.
[0146] In some embodiments, the volumetric particle size Dv50 of the above-mentioned lithium manganese iron phosphate seed crystals is 100nm~200nm.
[0147] In the process of preparing lithium manganese iron phosphate seed crystals, this application selects grinding and calcination processes, which is beneficial to obtaining lithium manganese iron phosphate seed crystals with good crystal form and suitable particle size. The lithium manganese iron phosphate seed crystals utilize the similarity of their crystal structure to lithium iron phosphate to provide a crystal growth platform for the subsequent formation of lithium iron phosphate on the surface of lithium manganese iron phosphate.
[0148] In this application, Dv50 refers to the cumulative volume of particles smaller than its diameter accounting for 50%, and the cumulative number of particles larger than its diameter accounting for 50%. It is also known as the median diameter and is commonly used to represent the average particle size. It can be measured using conventional methods in the art. As mentioned above, laser diffraction particle size analysis was selected for determination, specifically referring to standard GB / T19077-2016 to obtain the particle size distribution map, which was then calculated.
[0149] In these embodiments, this application discloses that the volumetric particle size Dv50 of lithium manganese iron phosphate seed crystals is any one of 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 152nm, 160nm, 170nm, 180nm, 190nm, and 200nm, or any one of the above two ranges.
[0150] In some embodiments, the above grinding is ultrafine grinding, wherein the ultrafine grinding is performed until the particle volume diameter (Dv50) is 0.1 μm to 3 μm.
[0151] The ultrafine grinding apparatus of this application includes conventional apparatus in the art, such as a sand mill. Specifically, a first iron source, a manganese source, a first phosphorus source, and a first lithium source are dispersed in a solvent and mixed to obtain a slurry. The solid content of the slurry is controlled, for example, to be 35% to 45%. The slurry is then ultrafinely ground using a sand mill until the particle size Dv50 is 0.1 μm to 3 μm. The precursor material is then dried.
[0152] The particle volumetric size Dv50 in this application has the same meaning as described above, and will not be repeated here. In these embodiments, this application discloses ultrafine grinding to a particle volumetric size Dv50 of any one of 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 2.0μm, or 3.0μm, or any one of the above two ranges.
[0153] In some embodiments, the ratio between the amount of phosphorus in the first phosphorus source and the sum of the amounts of iron in the first iron source and manganese in the manganese source is 1:(0.96~1).
[0154] In some embodiments, the ratio between the amount of lithium in the first lithium source and the sum of the amounts of iron in the first iron source and manganese in the manganese source is (1~1.05):1.
[0155] In some embodiments, the above-mentioned calcination is low-temperature calcination, wherein the temperature of the low-temperature calcination is 600℃~650℃ and the calcination time is 6h~15h.
[0156] The low-temperature roasting of this application is carried out in an inert atmosphere, during which the aforementioned precursor material forms lithium manganese iron phosphate seed crystals with good crystal form and suitable particle size.
[0157] In these embodiments, this application discloses that the low-temperature calcination temperature is any one of 600°C, 630°C, or 650°C, or any one of the ranges of both of the above.
[0158] In these embodiments, this application discloses a roasting time of any one of 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, and 15h, or any one of the ranges of both above.
[0159] In some embodiments of this application, it is disclosed that the prepared lithium manganese iron phosphate seed crystals are collected, dispersed together with a lubricant in a solvent, and wet-milled to obtain a mixed slurry B.
[0160] Add the second phosphorus source and the second lithium source to deionized water respectively, mix them evenly, then add the second iron source and continue stirring until completely dissolved to obtain mixed solution C;
[0161] Mixed slurry B and mixed solution C were mixed and homogenized for at least 20 minutes to obtain homogenized slurry D. This homogenized slurry D was then transferred to a high-temperature reactor. After purging the air from the reactor, it was sealed. The reactor was heated to the target temperature and held at that temperature for a hydrothermal reaction to obtain lithium iron phosphate coated with manganese iron phosphate. As described above, the specific surface area of this lithium iron phosphate coated manganese iron phosphate particles is 1.0 m². 2 / g~5.0m 2 / g.
[0162] The method for measuring the specific surface area of the lithium iron phosphate coated lithium manganese iron phosphate particles in this application includes any method conventional in the art. In these embodiments, this application discloses that the specific surface area of the lithium iron phosphate coated lithium manganese iron phosphate particles is 1.0 m². 2 / g, 1.27m 2 / g, 1.64m 2 / g, 1.79m 2 / g, 2.0m 2 / g, 2.45m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 4.98m 2 / g, 5.0m 2 Any one of / g or any one of the ranges of the above two.
[0163] In these embodiments, this application discloses that the Dv50 of the lithium iron phosphate coated lithium manganese iron phosphate particles is 100nm~300nm.
[0164] In these embodiments, this application discloses that the volumetric particle size Dv50 of lithium manganese iron phosphate seed crystals is any one of 100nm, 107nm, 110nm, 120nm, 130nm, 140nm, 150nm, 152nm, 160nm, 170nm, 173nm, 180nm, 190nm, 200nm, 229nm, 234nm, 250nm, and 300nm, or any one of the above two ranges.
[0165] In these embodiments, this application discloses that the ratio of the amount of phosphorus in the second phosphorus source to the amount of lithium in the second lithium source and the amount of iron in the second iron source is (1~1.05):(1~3):1.
[0166] The lubricant of this application is used to improve the dispersibility of lithium manganese iron phosphate seed crystals in a solvent. The type of lubricant includes any type conventional in the art, such as glycerin, PEG-200, PEG-400, PEG-600, and phenolic resin, or one or more of these. The amount of lubricant added is appropriate, for example, the mass of the lubricant is 0.1% to 2.0% of the mass of the lithium manganese iron phosphate seed crystal.
[0167] In some embodiments, the heating rate of the above-mentioned hydrothermal reaction is 1℃ / min to 5℃ / min, the temperature is raised to 160℃ to 240℃, and the hydrothermal reaction lasts for 10h to 24h.
[0168] This application employs a hydrothermal reaction method, that is, a liquid-phase method to grow a lithium iron phosphate coating layer on the surface of lithium manganese iron phosphate. This lithium iron phosphate coating layer has the characteristics of large coating area and uniform coating thickness.
[0169] In these embodiments, this application discloses that the heating rate of the hydrothermal reaction is any one of 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, or any one of the above two ranges.
[0170] In these embodiments, this application discloses heating to any one of 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C, or satisfying any one of the ranges of both above.
[0171] In these embodiments, this application discloses a hydrothermal reaction of any one of 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h, or any one of the ranges of both above.
[0172] In some embodiments, the first iron source and the second iron source are each independently selected from any one or more of ferrous sulfate, ferrous acetate, ferrous chloride, and ferrous nitrate.
[0173] In some embodiments, the first lithium source and the second lithium source are each independently selected from any one or more of lithium hydroxide, lithium acetate, lithium citrate, lithium dihydrogen phosphate, and lithium carbonate.
[0174] In some embodiments, the first phosphorus source and the second phosphorus source are each independently selected from any one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.
[0175] In some embodiments, the manganese source includes any one or more of manganese oxalate, manganese carbonate, manganese phosphate, ferrous manganese phosphate, and ferrous manganese oxalate.
[0176] In some embodiments, the solvent used to disperse the material includes one or more of ethanol, acetone, and butanone.
[0177] In some embodiments, this application discloses collecting the lithium iron phosphate coated lithium manganese iron phosphate particles prepared above, washing them with pure water until the pH of the washing solution is neutral and the conductivity is ≤100μs / cm, and obtaining a washed material. The washed material is then immersed in a metal salt solution, and a fluoride solution is slowly added while controlling the temperature at 75℃~85℃ and stirring continuously for 1.5h~2.5h. After filtration, the material is heated at 350℃~450℃ for 4h~6h to obtain lithium manganese iron phosphate coated with a fluorine passivation layer, and the fluorine passivation layer coats the surface of the lithium iron phosphate.
[0178] The purpose of using pure water washing in this application is to improve the product purity of lithium iron phosphate coated lithium manganese iron phosphate particles.
[0179] This application uses a liquid phase method to form uniformly distributed fluoride particles on the surface of lithium iron phosphate, and then heats and calcines them to obtain a uniformly coated fluorine-containing passivation layer.
[0180] In these embodiments, this application discloses that after the materials have been added, the temperature is controlled to be any one of 75°C, 78°C, 80°C, and 85°C, or any one of the above two ranges. The stirring time is controlled to be any one of 1.5h, 2h, and 2.5h, or any one of the above two ranges.
[0181] This application discloses in these embodiments that the heating and calcination temperature is any one of 350°C, 380°C, 400°C, 420°C, and 450°C, or any one of the above two ranges. The heating time is any one of 4h, 5h, and 6h, or any one of the above two ranges.
[0182] This application discloses in these embodiments that metal salts include one or more chlorides or nitrates of aluminum, lithium, and sodium.
[0183] This application discloses in these embodiments that fluorides include ammonium fluoride.
[0184] In some embodiments, this application discloses that the above-mentioned fluorine-passivated lithium manganese iron phosphate and carbon source are dispersed in deionized water, ball-milled, and then mixed to obtain a mixed slurry E1.
[0185] In some embodiments, this application discloses that the above-mentioned lithium manganese iron phosphate coated with fluorine passivation layer is dispersed in deionized water, and then ball-milled and mixed to obtain a mixed slurry E2.
[0186] In these embodiments, this application discloses a method of spray granulation and drying of mixed slurry E1 and mixed slurry E2, feeding the dried material into a box furnace, introducing an inert atmosphere, heating at 1.5℃ / min~2.5℃ / min to 300℃~450℃ and holding at that temperature for 0.5h~2h, then heating at 4℃ / min~6℃ / min to 650℃~750℃ and holding at that temperature for 10h~16h to obtain sintered material, subjecting the sintered material to air jet milling, and then sieving to remove iron, thereby obtaining lithium manganese iron phosphate material.
[0187] This application employs the above-described preparation method to deposit a carbon layer on the surface of a fluorine-containing passivation layer. This carbon layer itself possesses good conductivity, facilitating electron transfer between lithium manganese iron phosphate (LFP) materials and also facilitating electron transfer with active materials within the LFP material, such as LFP and LFe. Simultaneously, this carbon layer may or may not contain nitrogen. Compared to undoped carbon materials, nitrogen-doped carbon materials introduce active sites, further improving the electron and ion conduction capabilities of the LFP material.
[0188] Whether the carbon layer in this application contains nitrogen-doped carbon material or undoped carbon material, the carbon layer, together with the fluorine-containing passivation layer, is used to improve the structural stability and conductivity of lithium manganese iron phosphate material.
[0189] This application discloses, in these embodiments, the process of preparing the carbon layer, involving heating at any one of 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, or any one of the ranges of both above. The temperature is then increased to any one of 300℃, 350℃, 400℃, 450℃, or any one of the ranges of both above. The temperature is held for 0.5h, 1h, 2h, or any one of the ranges of both above. The temperature is then increased again at any one of 4℃ / min, 5℃ / min, 6℃ / min, or any one of the ranges of both above. The temperature is then increased to any one of 650℃, 700℃, 750℃, or any one of the ranges of both above. The temperature is then held for 10h, 11h, 12h, 13h, 14h, 15h, 16h, or any one of the ranges of both above.
[0190] In these embodiments, this application discloses that the carbon source includes one or more of sucrose, glucose, polyvinyl alcohol, gelatin, carbon nanotubes, graphene, and polyvinylpyrrolidone. In these embodiments, this application discloses that the amount of carbon source added is 3% to 20% of the mass of the lithium iron phosphate coated with manganese iron phosphate after washing and drying with pure water.
[0191] In these embodiments, this application discloses that the amount of carbon source added is any one of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20% of the mass of lithium iron phosphate coated with pure water after washing and drying, or any one of the above two ranges.
[0192] This application discloses in these embodiments that the nitrogen source includes melamine. This application also discloses in these embodiments that the mass ratio of the nitrogen source to the carbon source is 0.0015 to 0.01:1.
[0193] In these embodiments, this application discloses that the mass ratio of nitrogen source to carbon source is 0.0015:1, 0.01:1, or any one of the above two ranges.
[0194] Secondary batteries
[0195] [Positive electrode plate]
[0196] This application discloses a secondary battery in some embodiments, which includes a positive electrode sheet, a positive current collector, and a positive electrode film layer located on at least one side surface of the positive current collector. The positive electrode film layer includes the aforementioned lithium manganese iron phosphate material. This secondary battery simultaneously possesses the characteristics of good cycle performance and good specific capacity utilization.
[0197] In some embodiments of this application, the total mass of the positive electrode film is disclosed, wherein the mass percentage content of the above-mentioned lithium manganese iron phosphate material is 95% to 99%.
[0198] In these embodiments, this application discloses that, based on the total mass of the positive electrode film, the mass percentage content of the aforementioned lithium manganese iron phosphate material is any one of 95%, 96%, 97%, 98%, 99%, or any one of the ranges of both of the above.
[0199] In some embodiments, this application discloses that the positive electrode film layer, in addition to containing lithium manganese iron phosphate as the positive electrode active material, also includes a conductive agent and a binder. The conductive agent includes any one or more of graphite, carbon black, carbon dots, acetylene black, graphene, carbon nanotubes, and carbon nanofibers. The binder may include, but is not limited to, one or more combinations of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene ternary polymer, PVDF-hexafluoropropylene-tetrafluoroethylene ternary polymer, tetrafluoroethylene-hexafluoropropylene polymer, fluorinated acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, and carboxymethyl chitosan.
[0200] The positive electrode current collector of this application includes, but is not limited to, metal foil or composite current collector. The metal foil may be aluminum foil, and the composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material, such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0201] The method of forming the positive electrode film layer in this application includes mixing the above raw materials with a solvent (such as N-methylpyrrolidone) in a certain mass ratio to form a positive electrode slurry, uniformly coating the positive electrode slurry on both sides of the positive electrode current collector, controlling the coating weight on one side, and then compacting it to a certain compaction density using a cold press after drying, thereby obtaining a positive electrode sheet containing the positive electrode film layer.
[0202] [Negative electrode plate]
[0203] The negative electrode sheet includes a negative current collector and a negative electrode film layer located on at least one surface of the negative current collector. The negative electrode film layer includes a negative electrode active material, a conductive agent, a binder, and a dispersant. The negative electrode film layer of this application may be located on one or both sides of the negative current collector. The following discussion of the negative electrode film layer in this application is based on the assumption that it is located on both sides of the negative current collector.
[0204] The negative electrode active material in this application includes carbonaceous materials, which include one or more combinations of artificial graphite, natural graphite, soft carbon, and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, and hard carbon include any form of material conventional in the art, and include any manufacturer and model conventional in the art. Meanwhile, the negative electrode active material may also include silicon-based materials, which include one or two of silicon-oxygen materials or silicon-carbon materials. In addition, the negative electrode active material may also include silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 Li-Al alloys are used. However, this application is not limited to these materials; other conventional materials that can be used as negative electrode active materials for lithium-ion batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0205] The conductive agents in this application include any type conventional in the art, such as graphite, superconducting carbon, carbon black (e.g., acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene, and carbon nanofibers, or a combination of two or more of these. The dispersants in this application also include any type conventional in the art, such as cellulose and its salts, specifically including, but not limited to, methylcellulose, carboxymethylcellulose, hydroxyethylcellulose, sodium carboxymethylcellulose, lithium carboxymethylcellulose, etc. The binders in this application include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). Other optional additives may include thickeners (e.g., sodium carboxymethylcellulose CMC-Na), PTC thermistor materials, etc.
[0206] The negative electrode current collector in this application includes, but is not limited to, metal foil or composite current collector. The metal foil may be a copper foil, and the composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material, such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0207] The negative electrode film layer of this application is formed by coating, for example, dissolving the components including the negative electrode active material and other components into water to form a negative electrode slurry, coating the negative electrode slurry onto the two surfaces of the current collector, and obtaining the negative electrode film layer after drying and cold pressing.
[0208] [Electrolytes]
[0209] In the field of batteries, the electrolyte can be selected from at least one of solid electrolytes, gel electrolytes, and liquid electrolytes (i.e., electrolyte solutions). The secondary battery of this application uses a liquid electrolyte, i.e., an electrolyte solution.
[0210] Some embodiments of this application disclose an electrolyte comprising an electrolyte salt and an organic solvent. The electrolyte salt includes any type conventional in the art, such as, but not limited to, inorganic metal salts, such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2, etc.; fluorine-containing organometallic salts, such as LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropanedisulfonylimide lithium, cyclic 1,2-tetrafluoroethanedisulfonylimide lithium, LiN(CF3SO2)(C4F5SO2)2, etc. LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2, etc.; and metal salts containing dicarboxylic acid complexes, such as lithium bis(oxalate)borate, lithium difluorooxalate borate, lithium tri(oxalate)phosphate, lithium difluorobis(oxalate)phosphate, lithium tetrafluoro(oxalate)phosphate, etc.
[0211] According to some embodiments of this application, the concentration of the electrolyte salt in the electrolyte is 0.1 mol / L to 4 mol / L. In these embodiments, this application discloses that the concentration of the electrolyte salt is any one of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 2.8 mol / L, 3 mol / L, 3.2 mol / L, 3.5 mol / L, 3.8 mol / L, and 4 mol / L, or any one of the above ranges.
[0212] According to some embodiments of this application, the organic solvent comprises one or two of carbonates, carboxylic esters, nitrile solvents, and sulfone solvents. The carboxylic esters comprise one or more of ethyl acetate (EA), methyl acetate (MA), ethyl propionate (EP), propyl acetate (PA), methyl propionate (MP), methyl butyrate (MB), ethyl butyrate (EB), and 1,4-butyrolactone (GBL). The carbonates comprise one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl ethyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), and fluoroethylene carbonate (FEC). The nitrile solvents comprise one or more of acetonitrile (AN), glutaronitrile (GLN), and adiponitrile (ADN). Sulfone solvents include at least one or a combination of two of sulfolane (SF), dimethyl sulfone (MSM), ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0213] According to some embodiments of this application, the electrolyte further comprises a film-forming stabilizer, which includes a positive electrode film-forming stabilizer and a negative electrode film-forming stabilizer. The positive electrode film-forming stabilizer comprises carbonate additives and / or sulfate additives. The carbonate additives include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), vinyl ethylene carbonate (VEC), and dioctyl carbonate (CC). The sulfate additives include cyclic sulfonate additives and / or sulfated hydrocarbon ester additives; further, the cyclic sulfonate additives include one or more of 1,3-propanesulfonate lactone (PS), propenesulfonate lactone (PES), and 3-fluoro-1,3-propanesulfonate lactone (FPS); the sulfated hydrocarbon ester additives include one or more of vinyl sulfate (DTD), diethyl sulfate (DES), and dimethyl sulfate (DMS). The negative electrode film-forming stabilizer includes one or more of boron lithium salts, phosphorus-containing lithium salts, and sulfur-containing lithium salts; boron-containing lithium salts include one or more of lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), and lithium bis(oxalato)borate (LiDFOB); phosphorus-containing lithium salts include one or more of lithium difluorophosphate (LiPO2F2), lithium fluorophosphate (Li2PO3F), and lithium phosphate (Li3PO4). Sulfur-containing lithium salts include one or more of lithium fluorosulfonate (LiFSO3), lithium sulfate (Li2SO4), and lithium aminosulfonate (LiSO3NH2).
[0214] [Isolation Component]
[0215] In some embodiments, the secondary battery further includes a separator. This application does not impose any particular limitation on the type of separator; any known porous membrane with good chemical and mechanical stability can be selected.
[0216] In some embodiments, the separator includes a substrate material layer and a coating disposed on the surface of the substrate material layer; the substrate material layer includes one or more of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, and polyamide; the coating includes a ceramic coating and / or a polymer coating. The substrate material layer has good lithium-ion permeability, which is beneficial to lithium-ion migration; the coating disposed on the surface of the substrate material layer can further improve the mechanical properties of the separator. Optionally, the ceramic particles in the ceramic coating include one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2, and BaSO4. Optionally, the polymer material of the polymer coating includes one or more of polyethylene (PE), polypropylene (PP), poly(p-phenylene terephthalamide) (PPTA), polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI), and polyamide (PA). The polymer coating can be made of the same or different material as the substrate material layer, and the thicknesses of the polymer coating and the substrate material layer can be different. Optionally, the thickness of the polymer coating is less than the thickness of the substrate material layer.
[0217] In other embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0218] The secondary battery of this application will be described in detail below with reference to specific embodiments.
[0219] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0220] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0221] This application may employ conventional inorganic chemistry techniques within the art. In the following examples, efforts have been made to ensure the accuracy of the figures used (including quantities, temperatures, reaction times, etc.), but some experimental errors and biases should be considered. Temperatures (in degrees Celsius) used in the following examples are expressed in °C, and pressures are at or near atmospheric pressure. All reagents were purchased from AR-grade suppliers, and all reactions were carried out under argon protection. Unless otherwise stated, all reagents were obtained commercially.
[0222] Preparation Example 1-1
[0223] A lithium manganese iron phosphate material is provided, comprising the following preparation process:
[0224] S1. Disperse 5 mol of the first iron source (ferrous oxalate), 5 mol of the manganese source (manganese carbonate), 10 mol of the first phosphorus source (ammonium dihydrogen phosphate), and 5 mol of the first lithium source (lithium carbonate) into ethanol and mix well to obtain a slurry. Control the solid content of the slurry to be 40%.
[0225] S2. The mixture slurry is ultra-finely ground using a sand mill until the particle size Dv50 is 0.15μm. Subsequently, it is spray-dried with the equipment inlet air temperature controlled at 140℃, outlet air temperature at 80℃, spray compressed gas at nitrogen, and spray pressure at 0.3Mpa to obtain the precursor material. The precursor material is then placed in a box furnace containing an inert atmosphere and calcined at a low temperature of 600℃ for 7 hours to obtain lithium manganese iron phosphate seed crystals (particle size Dv50 of 152nm).
[0226] S3. Disperse the above-mentioned lithium manganese iron phosphate seed crystals together with 1% (by mass) lubricant PEG400 in pure water and wet grind them to obtain mixed slurry B; take 1.5 mol of the second phosphorus source (phosphoric acid) and 1.5 mol of the second lithium source (lithium hydroxide) and add them to deionized water respectively, mix them evenly, and then add 1.5 mol of the second iron source (ferrous sulfate), and continue stirring until completely dissolved to obtain mixed solution C; mix and homogenize mixed slurry B and mixed solution C, and control the homogenization time of the slurry to 2 hours to obtain homogenized slurry D;
[0227] S4. Transfer the homogeneous slurry D into a hydrothermal reactor, controlling the reactor filling degree to 70%. After purging the air from the reactor, seal it and heat the reactor to 200℃ at a heating rate of 3℃ / min, then carry out the hydrothermal reaction for 12 hours. This yields lithium iron phosphate coated manganese iron phosphate (the particle size Dv50 of this lithium iron phosphate coated manganese iron phosphate is 173 nm, and the specific surface area is 2.45 m²). 2 / g);
[0228] S5. Collect the lithium iron phosphate coated manganese iron phosphate particles prepared above, wash them with pure water until the pH of the washing solution is neutral and the conductivity is ≤100μs / cm, and obtain the washed material. Immerse the washed material in 2.4L of 0.1mol / L aluminum nitrate solution, and then slowly add 0.75L of 1mol / L ammonium fluoride solution. Control the temperature at 80℃ and stir continuously for 2h. Then filter and heat at 400℃ for 5h to obtain lithium manganese iron phosphate coated with a fluorine passivation layer, and the fluorine passivation layer is uniformly coated on the surface of lithium iron phosphate.
[0229] S6. Take the above-mentioned lithium manganese iron phosphate coated with fluorine passivation layer and sucrose (the mass of sucrose is 6% of the mass of the dried and washed material) and disperse them separately in deionized water, ball mill them, and then mix them to obtain mixed slurry E1. Take mixed slurry E1 for spray granulation and drying: centrifugal spray inlet temperature: 180℃, outlet temperature: 105℃, atomizer speed: 12000 r / min; put the centrifugally dried material into a box furnace, introduce an inert atmosphere, heat to 400℃ at 2.0℃ / min and hold for 1h, then heat to 700℃ at 5℃ / min and hold for 14h to obtain sintered material. The sintered material is subjected to air jet pulverization, then sieved to remove iron, and obtain lithium manganese iron phosphate material.
[0230] Preparation Examples 1-2
[0231] A lithium manganese iron phosphate material is provided, the preparation method of which differs from that of Preparation Example 1-1 in that, in S5, the washed material is immersed in 2.4 L of 0.04 mol / L aluminum nitrate solution, and then 0.75 L of 0.4 mol / L ammonium fluoride solution is slowly added. In S6, the mass of sucrose is 5% of the mass of the dried washed material, and other aspects remain the same as in Preparation Example 1-1.
[0232] Preparation Examples 1-3
[0233] A lithium manganese iron phosphate material is provided, the preparation method of which differs from that of Preparation Example 1-1 in that, in S5, the washed material is immersed in 2.4 L of 0.15 mol / L aluminum nitrate solution, and then 0.75 L of 1.5 mol / L ammonium fluoride solution is slowly added. In S6, the mass of sucrose is 10% of the mass of the dried washed material, and other aspects remain the same as in Preparation Example 1-1.
[0234] Comparative Preparation Example 1
[0235] A lithium manganese iron phosphate material is provided, the preparation method of which differs from that of Preparation Example 1-1 in that the core is not coated with lithium iron phosphate. The specific preparation process is as follows: S2: The mixture slurry is ground using a sand mill until the particle size Dv50 is 1 μm, followed by spray drying. The equipment inlet air temperature is controlled at 140℃, the outlet air temperature at 80℃, the spray compressed gas is nitrogen, and the spray pressure is 0.3 MPa, thus obtaining the precursor material. The precursor material is placed in a box furnace containing an inert atmosphere, and the calcination temperature is controlled at 720℃ for 7 hours to obtain lithium manganese iron phosphate seed crystals (volume size Dv50 of 311 nm). Furthermore, S3 and S4 of Preparation Example 1-1 are omitted, and S5 and S6 are performed directly, while the other preparation processes remain the same as those in Preparation Example 1-1.
[0236] Comparative Preparation Example 2
[0237] A lithium manganese iron phosphate material is provided, the preparation method of which differs from that of Preparation Example 1-1 in that the outer shell is not coated with a fluorine-containing passivation layer, while other aspects remain the same as those of Preparation Example 1-1.
[0238] Comparative preparation example 3
[0239] A lithium manganese iron phosphate material is provided, the preparation method of which differs from that of Preparation Example 1-1 in that the fluorine-containing passivation in the shell is replaced with 83.9g of aluminum oxide.
[0240] (1) Transmission electron microscopy test:
[0241] The lithium manganese iron phosphate material prepared in Example 1-1 was tested using a JEM-2100F transmission electron microscope (TEM). The working principle involves accelerating and focusing an electron beam onto the sample, causing scattering. The electron beam carries structural information about the sample, which is then collected and displayed on the screen. Sample preparation: The powdered sample to be tested was dispersed in anhydrous ethanol, then ultrasonically dispersed for 15 min, transferred to a copper grid, dried, and then tested. The test results are as follows: Figure 6 The diagram shows 6A and 6B.
[0242] (2) Testing the fluorine and carbon content of lithium manganese iron phosphate materials:
[0243] The elemental composition of lithium manganese iron phosphate material was analyzed using energy-dispersive X-ray spectroscopy (EDS) with an ISC150 model. Specifically, EDS was used to detect the material and perform point analysis; a scanning electron beam moved across the sample surface, recording the intensity of characteristic X-rays at different locations to generate an elemental distribution map for surface analysis; a detector collected characteristic X-rays and converted them into electrical signals, which were then processed by a multichannel pulse height analyzer. By detecting the energy distribution of these X-rays, the types of elements in the sample could be determined. By measuring the intensity of characteristic X-rays and comparing them with known standard samples, quantitative analysis of fluorine and carbon content could be achieved. The results are shown in Table 1-1 below:
[0244] Table 1-1 Element Content List
[0245]
[0246] As shown in Table 1-1, the raw materials used in preparation affect the elemental composition and content of the prepared products.
[0247] Preparation Example 2-1
[0248] A lithium manganese iron phosphate material is provided. Compared with preparation example 1-1, this lithium manganese iron phosphate material has the same fluorine and carbon content. The difference lies in the different particle size of the lithium manganese iron phosphate seed crystals in S2, and the different proportions of lithium iron phosphate and the different specific surface areas of lithium iron phosphate coated with lithium iron phosphate in S4. The preparation process of this lithium manganese iron phosphate material differs from that of preparation example 1-1 in that the calcination temperature in S2 is 600℃ and the calcination time is 4h. In S3, the molar mass of the second phosphorus source (phosphoric acid), the second lithium source (lithium hydroxide), and the second iron source (ferrous sulfate) are all 0.59 mol.
[0249] Preparation Example 2-2
[0250] A lithium manganese iron phosphate material is provided. Compared with preparation example 1-1, this lithium manganese iron phosphate material has the same fluorine and carbon content. The difference lies in the different particle size of the lithium manganese iron phosphate seed crystals in S2, and the different proportions of lithium iron phosphate and the different specific surface areas of the lithium iron phosphate-coated lithium manganese iron phosphate in S4. The preparation process of this lithium manganese iron phosphate material differs from that of preparation example 1-1 in that the calcination temperature in S2 is 630℃ and the calcination time is 6h. In S3, the molar mass of the second phosphorus source (phosphoric acid), the second lithium source (lithium hydroxide), and the second iron source (ferrous sulfate) are all 2.14 mol.
[0251] Preparation Examples 2-3
[0252] A lithium manganese iron phosphate material is provided. Compared with preparation example 1-1, this lithium manganese iron phosphate material has the same fluorine and carbon content. The difference lies in the different particle size of the lithium manganese iron phosphate seed crystals in S2, and the different proportions of lithium iron phosphate and the different specific surface areas of lithium iron phosphate coated with lithium iron phosphate in S4. The preparation process of this lithium manganese iron phosphate material differs from that of preparation example 1-1 in that the calcination temperature in S2 is 650℃ and the calcination time is 6h. In S3, the molar mass of the second phosphorus source (phosphoric acid), the second lithium source (lithium hydroxide), and the second iron source (ferrous sulfate) are all 0.49 mol.
[0253] (3) Test the Dv50 of lithium manganese iron phosphate seed crystals, the Dv50 and specific surface area of lithium manganese iron phosphate particles coated with lithium iron phosphate during the preparation process.
[0254] The test method for Dv50 is in accordance with GB / T19077-2016.
[0255] The test method for specific surface area is in accordance with GB / T 19587-2004.
[0256] (4) Test the lithium iron phosphate content in the lithium manganese iron phosphate material;
[0257] Assemble a 2032-type button cell according to the design method of the following embodiment. Using the Newway testing system, charge at 25°C with a constant current of 0.1C to 4.3V, then charge at a constant voltage of 4.3V to a current of 0.05C, let stand for 5 minutes, and then discharge at 0.1C to 2V. Obtain the charge-discharge curve at a current density of 0.1C. Manually mark the plateau intervals on the charging curve (e.g., 3.35~3.45V corresponds to the capacity contribution of iron, 4.05~4.15V corresponds to the capacity contribution of manganese), and measure the length of the above plateau intervals. Q(LFP)=Q(total 3.4V)-Q(LMFP 3.4V), Q(LMFP)=Q(4.1V)+Q(LMFP 3.4V), where the ratio of manganese to iron in lithium manganese iron phosphate and the theoretical specific capacity of both lithium iron phosphate and lithium manganese iron phosphate are known to be 170mAh / g. The masses of lithium iron phosphate and lithium manganese iron phosphate are W(LFP)=Q(LFP) / 170 and W(LMFP)=Q(LMFP) / 170, respectively. The final mass ratio of lithium iron phosphate to lithium manganese iron phosphate is R=W(LFP) / W(LMFP).
[0258] The following table 1-2 is obtained:
[0259] Table 1-2 Particle Size Distribution List
[0260]
[0261] As can be seen from Preparation Example 1 and Preparation Examples 2-2 and 2-3 in Table 1-2, the particle size of lithium manganese iron phosphate seed crystals increases with increasing calcination temperature.
[0262] Preparation Example 3-1
[0263] A lithium manganese iron phosphate material is provided, the structure of which differs from that of Preparation Example 1-1. In this material, a fluorine-containing passivation material and a carbon material constitute the outer shell to encapsulate the core. Furthermore, the mass percentage content of fluorine and carbon elements remains the same as in Preparation Example 1-1.
[0264] (5) Test for iron and manganese dissolution:
[0265] A 2032-type button cell was assembled according to the design method described in the following embodiment. Using a Newway testing system, it was charged at 25°C with a constant current of 0.1C to 4.3V, then charged at a constant voltage of 4.3V to a current of 0.05C. After resting for 5 minutes, it was discharged at 0.1C to 2V. After 50 cycles of the above steps, the cell was disassembled in an inert atmosphere glove box. The electrolyte was pipetted and placed in a sealed sample vial, then filtered through a 0.22µm filter membrane to remove any electrode material debris that might be present in the electrolyte. Finally, the manganese and iron content in the electrolyte was tested by ICP-OES (Inductively Coupled Plasma Emission Spectroscopy) to obtain manganese and iron dissolution data.
[0266] Table 1-3 is obtained.
[0267] Table 1-3 List of Iron and Manganese Elements Leakage
[0268]
[0269] As can be seen from the preparation examples and comparative examples in Tables 1-3, the design method provided in this application is beneficial to reducing the leaching of iron and manganese in lithium manganese iron phosphate materials, which means that the lithium manganese iron phosphate materials provided in this application have good structural stability.
[0270] Preparation Example 4-1
[0271] A lithium manganese iron phosphate material is provided, wherein the carbon material of the lithium manganese iron phosphate material is a nitrogen-doped carbon material. Specifically, in step S6, the lithium manganese iron phosphate coated with the above-mentioned fluorine passivation layer, sucrose (the mass of sucrose is 6% of the mass of the dried and washed material), and melamine (the mass of melamine is 0.3% of the mass of sucrose) are dispersed separately in deionized water, ball-milled, and then mixed to obtain a mixed slurry E2. Other aspects are the same as in preparation example 1-1. In the obtained lithium manganese iron phosphate material, the mass of nitrogen element is 1% of the mass of the nitrogen-doped carbon material.
[0272] (6) Testing powder resistivity: Powder resistivity tests were performed on the lithium manganese iron phosphate particles from Preparation Examples 1-1, 2-1, 3-1, and Comparative Preparation Examples 1 to 2.
[0273] Powder resistivity before ultrasound: Weigh 1g of lithium manganese iron phosphate particle samples from each example and comparative example and place them in a mold. Then place the mold in a four-probe resistivity tester and adjust the pressure to 8.0MPa. After the mold height and pressure are stable, test the forward resistivity and reverse resistivity of the positive electrode particle samples respectively, and take the average of the two as the powder resistivity of the lithium manganese iron phosphate particle samples.
[0274] Table 1-4 is obtained.
[0275] Table 1-4 Powder Resistivity List
[0276]
[0277] Based on Preparation Example 1-1, Preparation Example 2-1 and Comparative Preparation Example 1 in Table 1-4, since lithium iron phosphate has stronger conductivity than lithium manganese iron phosphate, the conductivity of the material decreases as the proportion of lithium iron phosphate in the lithium manganese iron phosphate material decreases.
[0278] Combining the preparation examples 1-1 and 4-1 in Table 1-4, it can be seen that the nitrogen-doped carbon coating layer introduces defect sites, which improves the conductivity, thus reducing the powder resistivity of lithium manganese iron phosphate material.
[0279] As can be seen from the preparation examples 1-1, 2, and 3 in Table 1-4, although the fluorine-containing passivation layer has a stable structure, it basically does not have electrical conductivity, which is why this application aims to control the content of the fluorine-containing passivation layer.
[0280] [Preparation of button cells]
[0281] 1. Positive electrode sheet: Lithium manganese iron phosphate particles from the above examples and comparative examples;
[0282] 2. Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 20:20:60. LiPF6 is then uniformly dissolved in this solution, and fluoroethylene carbonate (FEC) is added as an additive to obtain the electrolyte. The concentration of LiPF6 in this electrolyte is 1 mol / L, and the mass percentage of FEC in the electrolyte is 5%.
[0283] 3. Separating membrane
[0284] Polyethylene film is used as the separator.
[0285] 4. Preparation of button cells
[0286] Using the above-mentioned positive electrode as the working electrode and the lithium metal sheet as the counter electrode, the positive electrode, the separator and the lithium metal sheet are stacked in sequence, with the separator positioned between the working electrode and the counter electrode, and the above-mentioned electrolyte is injected to produce the button cells illustrated in Examples 1-1 to 4-1, and Comparative Examples 1 and 2.
[0287] (5) Discharge capacity test of button cells at 0.1C and 1C at 25℃:
[0288] Using the Shenzhen Xinwei Battery Testing System, at 25°C, the batteries corresponding to the examples and comparative examples were charged to 4.3V at a constant current of 0.1C, then charged to a current of 0.05C at a constant voltage of 4.3V. After resting for 5 minutes, they were discharged to 2V at 0.1C. The discharge capacity Q1 was recorded. Therefore, the discharge specific capacity = discharge capacity Q1 / mass of the positive electrode active material.
[0289] Using the Shenzhen Xinwei Battery Testing System, at 25°C, the batteries corresponding to the examples and comparative examples were charged at a constant current of 1C to 4.3V, then charged at a constant voltage of 4.3V to a current of 0.05C. After resting for 5 minutes, they were discharged at 1C to 2V. The discharge capacity Q2 was recorded. Therefore, the discharge specific capacity = discharge capacity Q2 / mass of the positive electrode active material.
[0290] (6) Capacity retention rate of button cell after 1000 cycles at 1C at 25℃:
[0291] Using the Shenzhen Xinwei Battery Testing System, at 25°C, the coin cells corresponding to the examples and comparative examples were charged at a constant current of 1C to 4.3V, then charged at a constant voltage of 4.3V to a current of 0.05C. After resting for 5 minutes, they were discharged at 1C to 2V. As above, the discharge capacity Q3 was calculated. After 1000 cycles under the above charge-discharge conditions, the discharge capacity on the 1000th cycle was Q3'. Therefore, the capacity retention rate = Q3' / Q3 × 100%.
[0292] The specific test results are shown in Table 2 below:
[0293] Table 2 Battery Performance List
[0294]
[0295] Based on Examples 1-1, 1-2, 1-3 and Comparative Examples 1, 2 and 3, it can be seen that the content of fluorine and carbon elements affects the performance of the battery, and the appropriate element content is beneficial to balancing the battery's cycle performance and specific capacity.
[0296] Based on Examples 1-1, 2-1, 2-2, 2-3, and Comparative Example 1, it can be seen that the suitable particle size of the lithium manganese iron phosphate seed crystals affects the particle size of the lithium manganese iron phosphate material during the preparation process. The particle size of the lithium manganese iron phosphate material affects the lithium ion transport distance in the solid phase, and also has an impact on the side reactions between the particles and the electrolyte. When the particle size is small, the lithium ion transport distance in the solid phase is short, the rate performance is good, and it is easy to achieve the specific capacity. However, its specific surface area is large, the contact area with the electrolyte is large, and the side reactions are intense, resulting in poor cycle stability. When the particle size is large, the specific capacity decreases, but the cycle performance is improved. This application needs to take into account multiple battery performances, so an appropriate range of particle size needs to be selected.
[0297] As can be seen from Examples 1-1 and 3-1, the layered coating design is more beneficial to the cycle performance and specific capacity of the battery.
[0298] As can be seen from Examples 1-1 and 4-1, the nitrogen-doped carbon coating layer is more beneficial to the cycle performance and specific capacity of the battery.
[0299] Therefore, this application provides a lithium manganese iron phosphate material with good structural stability and strong conductivity, which facilitates the battery to simultaneously achieve good cycle performance and specific capacity.
[0300] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A lithium manganese iron phosphate material, characterized in that: It includes a core and a shell, wherein the core is lithium iron phosphate coated with lithium manganese iron phosphate; The outer shell is located on at least a portion of the surface of the core; The outer shell comprises a fluorinated passivator and carbon material, wherein, based on the total mass of the lithium manganese iron phosphate material, the mass percentage content of fluorine is 0.5% to 2.0%, and the mass percentage content of carbon is 1.0% to 2.0%. Along the direction away from the core, the outer shell sequentially includes a fluorinated passivation layer and a carbon layer, the fluorinated passivation layer covering the surface of lithium iron phosphate, and the carbon layer covering the surface of the fluorinated passivation layer; The fluorine-containing passivation layer includes the fluorine passivation compound, and the carbon layer includes the carbon material.
2. The lithium manganese iron phosphate material according to claim 1, characterized in that: The fluorinated passivation material includes metal fluorides; The metal fluoride includes any one or more of aluminum fluoride, lithium fluoride, and sodium fluoride; and / or; The carbon material includes nitrogen-doped carbon material, and the mass percentage content of nitrogen element is 0.5% to 2.0% based on the total mass of the nitrogen-doped carbon material.
3. The lithium manganese iron phosphate material according to claim 1, characterized in that: The mass of the lithium iron phosphate is 11% to 43% of the mass of the lithium manganese iron phosphate.
4. The lithium manganese iron phosphate material according to claim 1, characterized in that: The specific surface area of the lithium iron phosphate coated manganese iron phosphate particles is 1.0 m². 2 / g~5.0m 2 / g.
5. A method for preparing lithium manganese iron phosphate material, characterized in that: Take the first iron source, manganese source, first phosphorus source and first lithium source and mix them evenly to obtain a mixture; The mixture was ground and calcined to obtain lithium manganese iron phosphate seed crystals. Lithium manganese iron phosphate coated with lithium iron phosphate is prepared by mixing a second iron source, a second phosphorus source, a second lithium source, and the aforementioned lithium manganese iron phosphate seed crystals and then reacting them with a hydrothermal reaction. Lithium manganese iron phosphate material is prepared by reacting the lithium iron phosphate-coated lithium manganese iron phosphate with fluorine-containing components and a carbon source.
6. The preparation method according to claim 5, characterized in that: The volumetric particle size Dv50 of the lithium manganese iron phosphate seed crystal is 100nm~200nm. And / or, the grinding is ultrafine grinding, wherein the ultrafine grinding is performed until the particle size Dv50 is 0.1μm~3μm; And / or, the calcination is a low-temperature calcination, wherein the temperature of the low-temperature calcination is 600℃~650℃ and the calcination time is 6h~15h.
7. The preparation method according to claim 5, characterized in that: The heating rate of the hydrothermal reaction is 1℃ / min~5℃ / min, the temperature is raised to 160℃~240℃, and the hydrothermal reaction lasts for 10h~24h. and / or; The first iron source and the second iron source are each independently selected from one or more of ferrous sulfate, ferrous acetate, ferrous chloride, and ferrous nitrate.
8. A secondary battery, characterized in that: The lithium manganese iron phosphate material includes any one of claims 1 to 4 or the lithium manganese iron phosphate material prepared by any one of claims 5 to 7.
9. An electrical device, characterized in that: Includes the secondary battery as described in claim 8.
Citation Information
Patent Citations
Nanometer lithium iron manganese phosphate composite material with core-shell structure, and preparation method and application thereof
CN105990562A
High-stability lithium manganese iron phosphate material and preparation method thereof, positive pole piece and lithium battery
CN118825226A